Design optimization for mass sizing of LEO communication satellites / Luqman Fathurrohim...[et al.] - Fathurrohim,, Luqman; Ridanto, Eko Poetro; Fariz, Ahmad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper focuses on the design optimization of communication satellites for the constellation in low earth orbit (LEO). The optimization starts with defining an objective function, which is the total mass of satellites, as a function of their orbit altitude, antenna transmit diameter, and nominal data rates. The optimization routine was done in order to minimize the total mass of satellites in order to reduce the total launch mass and the total cost. The use of three different design parameters has led to a genetic algorithm (GA) as an optimization method to find the best value for each design parameter. The results show that the optimization process using a genetic algorithm is successfully applied in solving complex multidisciplinary design problems such as the design of a communication satellite system with acceptable error.